Phenomenology of health - Biryukov, Viktor; Gozhenko, Anatolii; Anchev, Anatolii; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Health, as a phenomenon of a planetary scale, reflects the life of mankind, the world of animals and plants. Human health issues from the mid-20th century began to come out of the exclusive medical control. The increase in the average life expectancy of the population of developed countries, the globalization of economic, political, cultural life, the emergence of pandemics of viral infections - all these factors have shown that in maintaining the health of the population, the actual medical contribution is no more than 10%. The rest of the influence is exerted by economic, environmental, social and hereditary factors. The burden of disease of the population causes significant damage to the economies of even the most developed countries. Human health is a comprehensive, integrative assessment of the quality of his being for each specific time and age period. Thus, we consider health as a derivative of the ontogenetic scale. A feature of this scale is the unification on the time axis (x) of both calendar and biological ages. The axis (y) reflects the magnitudes of the influence of known determinants of health that accompany a person at each stage of his ontogenetic movement. One of the most important conditions for the functioning of the human body and animals is the constancy of the internal environment, defined as homeostasis. It is thanks to homeostasis that every cell of the body is in a relatively constant environment, which is an extracellular fluid. Earlier we drew attention to the fact that all the parameters of extracellular fluid can be divided into indicators of water-salt homeostasis (osmolality, concentrations of ions Na, K, Ca, pH). The task of water-salt homeostasis is to ensure water balance, both intracellular water content and the total amount in the body. The second group of homeostasis indicators is represented by metabolites (glucose, lipids, amino acids, proteins, urea, creatinine, bilirubin, etc.). On the one hand, metabolic indicators are quite stable, which made it possible to attribute them to homeostasis, but on the other hand, their most important feature is that they are very closely related to the functional state of the body (organs, tissues, cells), since the main task of metabolism is to adequately provide the organs and tissues of functioning systems with the necessary amount of energy and plastic substrates. Accordingly, with changing functions, the levels of the main metabolites should also change. At the same time, the main criterion for the adequacy of the metabolic support of functioning systems is not their homeostating concentration, but compliance with the changing needs of organs and tissues. That is, in the body it is necessary to ensure a sufficiently strong relationship between function and metabolism. In the literature, the subjective assessment of whether social factors affecting health can be avoided through structural changes in policy and practice appears to be the dominant way to determine the social determinant of health. In addition, the term "social" remains ambiguous and difficult to define within the clear boundaries of health care. There are already concerns about the requirements and approaches to their screening, as well as their benefits and unintended harm. A long list of CLE can prevent doctors from prioritizing screening for social determinants and referring patients to support services. Politicians may also be less inclined to continue working with such a long and growing list. In most government agencies, there are inherent barriers to adopting a social determinant approach in policymaking. A long list can add additional restrictions on adoption. A clear understanding of the "social determinants of health" is critical for all key stakeholders, including the public.